Randomized controlled trial: comparison of two surgical techniques for closing the wound following ileostomy closure: purse string vs direct suture. (29th August 2013) - Dusch, N.; Goranova, D.; Herrle, F.; Niedergethmann, M.; Kienle, P.
Abstract Aim Surgical site infection (SSI) is a common complication following ileostomy closure with a frequency of up to 40%. This prospective randomized controlled trial was initiated to compare two surgical techniques – direct suture (DS) and purse‐string suture (PSS) – used to close the wound following ileostomy closure. The primary end‐point was the SSI rate. Secondary end‐points were cosmetic outcome [using two validated scales: the Patient and Observer Scar Assessment Scale (POSAS) and the Body Image Questionnaire (BIQ)] and the influence of other factors on the SSI rate. Method Of a total of 99 patients screened, 84 were included in this study. Forty‐three patients were randomized into the PSS group and 41 were randomized into the DS group. Follow up was performed within 3 days after surgery, at discharge, and 30 days and 6 months after the operation. Results In the PSS group there were no cases of SSI compared with 10 (24%) cases in the DS group (P = 0.0004). There were no statistically significant differences in cosmetic outcome between the two groups. No other statistically significant factors influencing the incidence of SSI could be identified. Conclusion The rate of SSI is significantly lower following PSS than following DS, and both techniques have a similar cosmetic outcome. PSS closure should be considered as standard of care for wound closure after ileostomy reversal.